A multifunctional synergy development evaluation model of the impact of the cascade reservoir construction sequence on basins - Wanjie Zhao; Donglin Li; Yuanjian Wang; Enhui Jiang; Yanhui Liu; Jieyu Li; Qiang Wang (Ecological Indicators, 2024)
Considering the mass reservoirs construction, it is important to study the cascade reservoir construction sequence, which directly affects the water and sediment resource allocation, ecological environment restoration, and socioeconomic development of the basin. Thus, we constructed an evaluation index system by comprehensively considering the basin water and sediment discharge index, basin ecological and environmental maintenance index, and basin social and economic development index. The evaluation model was established to assess the impact of the cascade reservoir construction sequence on basin multifunctional synergy development index. The model was applied to evaluate the cascade reservoir construction sequence in the Yangtze and Yellow River Basin of China. The results revealed that: (1) The basin water and sediment discharge index, basin social and economic development index, and basin multifunctional synergy development index benefits gradually increased, the basin ecological and environmental maintenance index benefits progressively decreased in the Yangtze and Yellow River Basin. (2) The basin water and sediment discharge index, and basin ecological and environmental maintenance index of the planned cascade reservoir construction sequence ranked top in the Yellow River Basin; the basin water and sediment discharge index, and basin social and economic development index of the planned cascade reservoir construction sequence ranked top in the Yangtze River Basin. (3) The cascade reservoir construction sequence focused more on basin social and economic development index benefits when the level of national economic development was low, and more on basin water and sediment discharge index benefits when it was high. (4) Reservoir capacity and installed capacity were the main factors influencing the cascade reservoir construction sequence in the Yangtze and Yellow River Basin, respectively. These findings provide useful information regarding the cascade reservoir construction sequence.